Pandemic, political and capitalism. Lessons in times of social confinement. (Publicatio UEPG: Ciências Sociais Aplicadas, 2020)
In the present work, we propose to carry out some provisional analyzes regarding the COVID-19 pandemic. To do this, we made a tour around the issue of confinement and the relationship of society with TICs. Second, we think about global development in its geopolitical and economic aspects, and then we analyze the relationship between fear (fear of contagion, fear of contagion) as a political resource. Finally, we address some aspects related to the construction of democratic systems, fundamentally we describe the forms of intervention that the State has had in this pandemic. Finally, we refer to three aspects that, in our opinion, denote the current health situation: the question of inequality, the risk society and its impacts on political management.